(3GdLhGHGJ GdhGajI HGdHQGgjf GdTGajIs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3bGd GdEeGe GdeDjO HGddg jMji Hf MeRI GdMeO ddg GdPi ChQOfG MjGV GdeYQaI hcQYfG ai fejQgG GdYPH GdSdSGd s
(3BNQgG (B:s
(3hcGf LGQjkG Ydi CUhdg , hde jNGda ELeGYkG bGWYkG agPG eG CQOfG PcQg ai gPg GdeSGFd Gfg bQjH eLjO s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GdfSNI HgG MhGTs
(3cJHJ HYV GdYfGhjf HGdMeQIs
(3hYdi MhGTjgG HYV GdJYdjbGJ s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis